Pulsed electromagnetic fields combined with a collagenous scaffold and bone marrow concentrate enhance osteochondral regeneration: an in vivo study - Veronesi, Francesca (BMC Musculoskelet Disord, 2015)
BACKGROUND: The study aimed to evaluate the combined effect of Pulsed Electromagnetic Field (PEMF) biophysical stimulation and bone marrow concentrate (BMC) in osteochondral defect healing in comparison to the treatment with scaffold alone. METHODS: An osteochondral lesion of both knees was performed in ten rabbits. One was treated with a collagen scaffold alone and the other with scaffold seeded with BMC. Half of the animals were stimulated by PEMFs (75 Hz, 1.5 mT, 4 h/day) and at 40 d, macroscopic, histological and histomorphometric analyses were performed to evaluate osteochondral defect regeneration. RESULTS: Regarding cartilage, the addition of BMC to the scaffold improved cell parameters and the PEMF stimulation improved both cell and matrix parameters compared with scaffold alone. The combination of BMC and PEMFs further improved osteochondral regeneration: there was an improvement in macroscopic, cartilage cellularity and matrix parameters and a reduction in the percentage of cartilage under the tidemark. Epiphyseal bone healing improved in all the osteochondral defects regardless of treatment, although PEMFs alone did not significantly improve the reconstruction of subchondral bone in comparison to treatment with scaffold alone. CONCLUSIONS: Results show that BMC and PEMFs might have a separate effect on osteochondral regeneration, but it seems that they have a greater effect when used together. Biophysical stimulation is a non-invasive therapy, free from side effects and should be started soon after BMC transplantation to increase the quality of the regenerated tissue. However, because this is the first explorative study on the combination of a biological and a biophysical treatment for osteochondral regeneration, future preclinical and clinical research should be focused on this topic to explore mechanisms of action and the correct clinical translation.